Non-steroid anti-infflamatory drugs in municipal wastewater and surface waters = Niesteroidowe leki przeciwzapalne w ściekach miejskich i wodach powierzchniowych - Płuciennik-Koropczuk, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Increased production and consumption of drugs influences the pollution pharmaceuticals. Recent years have seen a significant increase in the consumption of non-prescription medicines, among which, are a large group of non-steroidal anti-inflammatory drugs (NSAIDs).
Keywords: zanieczyszczenie farmaceutykami; niesteroidowe leki przeciwzapalne; ścieki miejskie; wody powierzchniowe; pharmaceuticals pollution; NSAIDs; wasterwater; surface waters